Using interprofessional education to build dynamic teams to help drive collaborative, coordinated and effective newborn care - Josephine Langton; Sara Liaghati-Mobarhan; Edith Gicheha; Jennifer Werdenberg-Hall; June Madete; George Banda; Elizabeth M. Molyneux; the NEST360 Education Team (BMC Pediatrics, 2023)
Abstract Background As countries strive to achieve sustainable development goal 3.2, high-quality medical education is crucial for high-quality neonatal care. Women are encouraged to deliver in health units attended by a skilled team. Traditionally, the team is doctors and nurses, but they are members of a large group of interdependent experts from other disciplines. Each discipline trains separately, yet the goal of good neonatal care is common to all. The use of interprofessional education breaks down these professional silos improving collaborative practice and promoting excellent clinical care. Introduction of new educational materials and training requires a rigorous approach to ensure sustainability. Methods An extensive needs assessment identified gaps in neonatal training. Specifically, there was a lack of inclusion of medical devices used in clinical care. In each country, national key stakeholders came together to develop and revise their own neonatal curricula, trainings or guidelines. A core writing education team were tasked to develop evidence-based materials on pertinent medical devices to include in these national materials. These then underwent internal and external review. A provider course for biomedical engineers and technicians was introduced. Skills labs were established to improve practical skills teaching. To improve the quality of teaching, a NEST360 generic instructors course (GIC) was developed. Results Twenty modules, 14 scenarios, 17 job aids and 34 videos have been published to date. Materials have been embedded into neonatal curricula and national trainings. Forty-one skills labs were installed in pre-service learning institutions and, up to June 2022, have been used by 7281 students. Pre- and in-service interprofessional training was implemented at all NEST360 institutions (clinical and biomedical). GIC courses were conducted at least twice a year in all countries. Three hundred seventeen nurses, biomedical and clinical staff have undertaken the GIC in all four countries. GIC participants report that the course has very positively influenced their teaching practice. Conclusions Inclusion of key stakeholders throughout has ensured training is embedded within the four countries. Use of interprofessional education and inclusion of biomedical engineers and technicians has been very successful. Introduction of the GIC has developed a pool of high-quality educators for neonatal care. This approach has ensured that high-quality interprofessional neonatal training is included within national agendas for neonatal care and beyond.